Surgical eye camp in rural area of Nepal and its role in Vision 2020 (Journal of Basic and Applied Research in Biomedicine, 2022)
Blindness continues to remain a major public health problem in Nepal and cataract is the leading cause. Cataract surgical coverage is relatively low in the rural areas where prevalence of blindness is high. This is a descriptive cross sectional camp based study in a remote village of Nepal, where 4 days screening of the eye disease mainly the cataract was done. The aim of the study was to evaluate the role of surgical outreached eye camps in rural Nepal and its impact in Vision 2020. 250 patients (54.80% males and 45.20% females) underwent eye health screening tests. Cataract was the commonest ocular disease (29.6%) among the screened population and 24% (60 patients) of them required cataract surgery (57% male and 43% female). The mean age of the operated patient was 71.84 ± 10.6years. Among the operated cases, bilateral blindness was present in 21.66% and unilateral blindness in 70% but after vision restoring cataract surgery, normal visual acuity (6/6-6/18) was achieved in 31(51.66%), and vision of 6/24-6/60 in 23 (38.33%) cases. Cataract remains to be the major cause of blindness in Nepal and arrangement of repeated surgical eye camps in the remote areas of Nepal could aid in reducing the preventable cause of blindness thereby help in achieving the goal of Vision 2020.